The feasibility of resistivity responses as fluid monitoring controlled system in conventional reservoir-hydrocarbon production - Hasan, K.A. (Offshore Technology Conference, 2020)
During field recovery optimization, EOR takes a role to keep active and always develop the techniques for increasing oil production from time to time. Foam flooding has been introduced as a new technique to overcome the limitation of gas injection by reducing gas mobility. Specifically, the foam injection was a success to optimize the recovery. Unfortunately, the utilization of foam creates several challenges, especially in the foam monitoring system. Resistivity analysis is the best parameters used for generating the foam system monitoring. This study was focusing on identifying the major controlling factor which donates to resistivity responses. Characteristic of the resistivity responses towards the fluid's injection as the function of the variances in fluids type with the divergence of reservoir properties (i.e., porosity and permeability) is the primary objectives in this study. Variances in type fluids and reservoir properties were applied in this study for enhancing the application of this project in global used. Competent clastic reservoirs samples were used in this study (Idoha and Berea), which resistivity responses was determined using the equipment rig for all samples in 4 saturation (Air, Brine, and Foam in concentration 0.5 wt, 1.0 wt). Resistivity measurement was conducted as a function of foam injection time to determine the correlation of foam propagation in porous media based on the resistivity difference in two reservoir condition. Generally, the resistivity of dry condition (air saturation) is higher as compared to the wet condition. Storage capacity, fluids integrity (density, viscosity, interfacial tension, and the concentration) and mix fluids windows are the most factors which influence the resistivity responses. Fluids integrity have been controlled by chemical and physical properties of the fluids, i.e., density, viscosity, interfacial tension, and the concentration. All features donate the producing of fluids resistivity responses. All parameters were sensitive to temperature changes. Foam monitoring, wherein the positive side the resistivity responses are important tools in fluids determination due to detailed answers for each condition. Copyright Â© 2020, Offshore Technology Conference.